WAYS OF THE ORIGIN OF SYNONYMS IN FRENCH (Academia Science Repository, 2023)
In this paper, an attempt is made to describe some synonymous series of the modern French language, consisting of syntactic constructions of "secondary predication" and subordinate clauses. This study is the first experience of scientific study and description of the undeveloped issues of Mari linguistics – grammatical synonymy. The paper theoretically comprehends and summarizes in a synchronous aspect the features of the formation of synonymic series, provides a description of grammatical synonyms at the level of case and case-post-syllabic forms.